SOLITON STRUCTURES OF SOME GENERALIZED NONLINEAR DISPERSION EVOLUTION SYSTEMS - İnç, Mustafa; Kilic, Bulent (Editura Acad Romane, 2015)
Some special soliton solutions of nonlinear dispersion Drinfel'd-Sokolov and generalized Maccari systems are obtained by means of the functional variable method. Several exact solutions of the mentioned nonlinear evolution systems are acquired, such as compacton-type solutions and solitary and periodic waveforms.
Keywords: Drinfel'd-Sokolov system; Maccari system; functional variable method